Awareness of Emerging Glanders in Horses in Indonesia - Susan Maphilindawati Noor; T Ariyanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Glanders is a zoonotic disease that is highly contagious in animals and humans, caused by Burkholderia mallei. The clinical manifestations of glanders in horses are in the form of lesions on skin, nose and lungs. Horses play a role in transmitting glanders to healthy animal populations around them due to latent infections. Infection of glanders in humans is acute causing respiratory failure and could be fatal without proper treatment. Recently re-emerging glanders is reported in several countries that have eradicated diseases such as in India, Germany and China. The status of glanders in Indonesia is declared free, but surveillance showed positive antibodies to B. mallei in horses, as had been reported in 1939 and in 2018 in Jakarta. Glanders has a negative impact on a country's economy resulting in restrictions on international trade. Prevention of emerging glanders to Indonesia needs to be alerted because there is no effective treatment, no vaccines available for prevention and causing negative economic impacts. This paper aims to discuss glanders in horses, countermeasures through monitoring and surveillance, early detection in order to increase awareness of emerging glanders in Indonesia.